Wojna z terroryzmem a filozofia prawa. Uwagi na marginesie wydarzeń po 11 września 2001 r. - Dobrzeniecki, Karol (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The article examines to what extend existing philosophy of law and especially natural law doctrine may be applied in the discourse on legitimization of a state fighting terrorism. Since the 9-11 attacks issues of extraordinary threats to public safety occur regularly in scientific discussions among ethics, sociologists, political scientists, security experts. This topic has also became visible in legal science, even in its most unworldly discipline which is philosophy of law. The article is intended to present general tendencies in legal discussions after 9-11 with special reference to aristotelic-tomistic tradition of understanding the notions of common good, the aim of a state and of law.